AVALON: The Italian cohort study on real‐life efficacy of hypomethylating agents plus venetoclax in newly diagnosed or relapsed/refractory patients with acute myeloid leukemia. Issue 7 (24th January 2023) - Todisco, Elisabetta; Papayannidis, Cristina; Fracchiolla, Nicola; Petracci, Elisabetta; Zingaretti, Chiara; Vetro, Calogero; Martelli, Maria Paola; Zappasodi, Patrizia; Di Renzo, Nicola; Gallo, Susanna; Audisio, Ernesta; Griguolo, Davide; et al.
Abstract: Background: Venetoclax in combination with hypomethylating agents (HMA) is revolutionizing the therapy of acute myeloid leukemia (AML). However, evidence on large sets of patients is lacking, especially in relapsed or refractory leukemia. Methods: AVALON is a multicentric cohort study that was conducted in Italy on patients with AML who received venetoclax‐based therapies from 2015 to 2020. The study was approved by the ethics committee of the participating institution and was conducted in accordance with the Declaration of Helsinki. The effectiveness and toxicity of venetoclax + HMA in 190 (43 newly diagnosed, 68 refractory, and 79 relapsed) patients with AML are reported here. Results: In the newly diagnosed AML, the overall response rate and survival confirmed the brilliant results demonstrated in VIALE‐A. In the relapsed or refractory AML, the combination demonstrated a surprisingly complete remission rate (44.1% in refractory and 39.7% in relapsed evaluable patients) and conferred to treated patients a good expectation of survival. Toxicities were overall manageable, and most incidents occurred in the first 60 days of therapy. Infections were confirmed as the most common nonhematologic adverse event. Conclusions: Real‐life data show that the combination of venetoclax and HMA offers an expectation of remission and long‐term survival to elderly, newly diagnosed patients, and to relapsed or chemoresistant AML, increasing the chance of cure through a different mechanism of action. The venetoclax + HMA combination is expected to constitute the base for triplet combinations and integration of target therapies. Our data contribute to ameliorate the understanding of venetoclax + HMA effectiveness and toxicities in real life. Abstract : This is an Italian multicentric cohort study evaluating efficacy and safety of venetoclax + hypomethylating agents (HMA) in a real‐life setting of newly diagnosed, relapsed, and refractory patients with acute myeloid leukemia (AML). The data show that the combination of venetoclax and HMA offers an expectation of remission and long‐term survival not only to newly diagnosed but also to relapsed or refractory elderly patients with AML.